Test of Acceptance of Batawoli-Based Nugget Modificationslocal Food Materials Milk Fish (Chanos Chanos) as Alternative Snack For Stunting Toddlers - Mutiara Devyntha Putri Koestya; Taufiqurrahman; nur hatijah; Inne Soesanti (Politeknik Kesehatan Kemenkes Surabaya, 2024)
Stunting, a growth disorder in children characterized by height or length below the standard for their age, can be prevented by ensuring adequate intake of energy and protein. This study aims to assess the acceptability of modified Batawoli nuggets as a potential snack alternative for toddlers with stunting. The research employed a true experimental design with control and treatment groups. Organoleptic tests were conducted on Batawoli nugget formulations with varying ratios: F0 (1:0:1:1), F1 (1:2:1:1), F2 (1:1:1:1), and F3 (2:1:1:1). Data analysis utilized the Mann Whitney test. The findings reveal organoleptic test scores for each formulation: F0 scored 3.35 (somewhat liked), F1 scored 3.9 (somewhat liked), F2 scored 3.46 (somewhat liked), and F3 scored 3.52 (somewhat liked). The study concludes that the most preferred formulation, based on all indicators, is F1 (1:2:1:1), which provides an energy value of 3.5 kcal/g (>1.5 kcal/g) and a Protein Efficiency Ratio of 12.6% (within the range of 10% - 16%). Consequently, this formulation presents a promising local complementary food option for toddlers with stunting.